Determinação das coordenadas dos vértices limítrofes de imóveis rurais utilizando-se do posicionamento GPS - Ishikawa, Mauro Issamo [UNESP]; Barros, Zacarias Xavier de [UNESP] (EIA Energy in Agriculture, 2010)
Aiming to evaluate the methodologies of surveys related with the specifications of Geo-referencing Rural Parcels in Brazil, established by INCRA (National Institute of Colonization and Agrarian Reform), in attendance to the Law 10.267/01, and considering aspects of precision and accuracy, a test area was set up in the Assentamento Florestan Fernandes, in the county of Presidente Bernardes, SP. This area was subdivided in three sub-areas in order to simulate the existence of three contiguous rural parcels. The first stage of work consisted in the implantation and determination of the control points coordinates in their respective areas. These control points were determined by the process of direct transport, using dual frequency (L1/L2) GPS receivers and through the process of traverse with baselines of up to 20 km, using single frequency receivers (L1). The coordinates of the points of the perimeter of the three sub-areas were determined using single frequency GPS receivers, from two survey methods, both using static relative positioning. The first one, so called traverse, each point that delimits the property was occupied successively, starting from the control point and closing at another. In other, denominated double irradiation, each point of the property was irradiated from two control points. These procedures were accomplished with the intention to define and to implement a mistake control strategy, to realize redundancy measurements and to use an adjustment method correctly, to obtain trustworthily values in the patterns demanded in each kind of survey. With the data collected and processed some analyses could be accomplished from the discrepancies between the coordinates obtained by different methodologies. The results show that this test area may be used to validate other methodologies and equipments. The results were satisfactory and attended the specifications of Geo-referencing Rural Parcel.

Visando avaliar metodologias de levantamentos incluídos na Norma Técnica para Georreferenciamento de Imóveis Rurais, estabelecidos pelo INCRA, em atendimento a Lei n. 10.267/01, e considerando aspectos de precisão e acurácia, uma área teste foi implantada no Assentamento Florestan Fernandes, no município de Presidente Bernardes, SP. Essa área foi subdividida em três subáreas de modo a simular a existência de três imóveis contíguos. A primeira etapa do trabalho consistiu na implantação e determinação das coordenadas dos vértices de apoio básico nas respectivas áreas. Esses vértices foram determinados a partir do processo de transporte direto, utilizando-se receptores de dupla frequência (L1/L2) e através do processo de poligonal com linhas de base não superior a 20 km, com receptores de simples freqüência (L1). As coordenadas dos vértices limítrofes das três subáreas foram determinadas utilizando-se GPS de simples freqüência, a partir de dois processos de levantamento, ambos utilizando o método de posicionamento relativo estático. O primeiro, denominado de poligonação, teve cada vértice que delimita a propriedade ocupada sucessivamente, partindo-se de um ponto de apoio básico e fechando em outro. No segundo, com duplas linhas de base, ou seja, dupla irradiação, cada vértice limítrofe da propriedade foi irradiado a partir de dois vértices do apoio básico. Esses procedimentos foram realizados com o intuito de se definir e implementar uma estratégia de controle de erros, realizar medidas redundantes e empregar um método de ajustamento adequado, para que seja possível obter valores confiáveis dentro dos padrões exigidos em cada tipo de levantamento. Com os dados coletados e processados, algumas análises foram realizadas a partir das discrepâncias entre as coordenadas obtidas por diferentes metodologias GPS. Os resultados foram considerados satisfatórios e atenderam às prescrições da Norma Técnica.
Determination of the coordinates of points limits of rural parcels using positioning GPS
Keywords: Law 10267/2001; Geo-referencing rural parcels; GPS; Lei n. 10267/2001; Georreferenciamento de imóveis rurais; GPS